An optimized 128-bit cellular automata-based hash function for authentication of data at rest and in transit - Surendra Kumar Nanda; Suneeta Mohanty; Prasant Kumar Pattnaik (Institute of Advanced Engineering and Science, 2023)
The cryptographic hash functions are the most fundamental cryptographic concept. These functions are used as basic building blocks for digital signatures and message authentication. Boolean functions are the core of hash functions. These functions are expected to provide pseudo-randomness as well as input sensitivity. Cellular automata are a form of Boolean function that exhibits strong cryptography properties as well as chaotic behavior. This paper proposes a hash function, designed on the principle of cellular automata. The proposed algorithm is secure and meets the requirements for a successful hashing scheme. The hash function has strong statistical and cryptographic characteristics, according to the findings of the avalanche test and the National Institute of Standards and Technology (NIST) Statistical Test Suite. The modularity of different operations of this algorithm makes it suitable for a high-capacity processing environment to produce efficient performance.